2021
DOI: 10.1016/j.wneu.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

High TRAF3IP3 Level Predicts Poor Prognosis of Patients with Gliomas

Abstract: Purpose: TRAF3IP3 is involved in the maturation of immune cells, the development of immune tissues and the immune response of the body. TRAF3IP3 is shown to expressed in a variety of malignant tumor cell lines. Down-regulated expression of TRAF3IP3 in malignant melanoma can inhibit tumor growth. However, the role of TRAF3IP3 in glioma is still unknown. In this study, we aimed to study the relationship between TRAF3IP3 and glioma based on TCGA data. Method: We used the Wilcoxon rank sum test to compare the expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…High protein level of TRAF3IP3 promotes melanoma growth [28]. In patients with glioma, TRAF3IP3 stimulates cell proliferation via ERK signaling pathway and high expression of TRAF3IP3 predict a poor prognosis [29,30]. In our study, TRAF3IP3 expression was negatively associate with T stage and N stage of breast cancer patients.…”
Section: Discussionsupporting
confidence: 54%
“…High protein level of TRAF3IP3 promotes melanoma growth [28]. In patients with glioma, TRAF3IP3 stimulates cell proliferation via ERK signaling pathway and high expression of TRAF3IP3 predict a poor prognosis [29,30]. In our study, TRAF3IP3 expression was negatively associate with T stage and N stage of breast cancer patients.…”
Section: Discussionsupporting
confidence: 54%
“…TRAF3IP3 expression is significantly higher in melanoma than in normal tissues (10). Yang et al previously reported that high TRAF3IP3 expression in patients with glioma might be associated with poorer prognoses (39). Compared to the study by Yang et al, our study is more in-depth and detailed with regard to bioinformatic analyses.…”
Section: Discussionmentioning
confidence: 77%
“…Recent studies have shown that TRAF3IP3 is involved in B and T cell development and for maintaining the functional stability of regulatory T cells [ 46 , 47 ]. TRAF3IP3 has been shown to function as an oncogene in melanoma and glioma [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%